World Englishes, heterodoxy, and applied linguistics - Jenks, Christopher (World Englishes, 2025)
It is understandable that many people find it challenging to adopt a positive moral position with regard to English and its role in the world. The language is used in many contexts and situations to prop up systems of discrimination and inequality, leading to negative material and symbolic outcomes. Although these negative aspects of English must remain at the core of what scholars investigate, there are reasons why it is necessary to complement such interests with scholarship that is informed by other moral positions. To this end, the current article introduces linguistic optimism to account for the contexts and situations that English plays a positive role. Using portraits of hope that are based on the author's experiences working in six distinct geopolitical contexts, it is argued that an eclectic array of moral positions are needed to be faithful to the rich ethnolinguistic diversity that characterizes interlocutors of world Englishes.